Salafism and traditionalism: scholarly authority in modern Islam - Hamdeh, Emad (Cambridge University Press, 2021)
"One of the most contentious topics in modern Islam is whether one should adhere to an Islamic legal school or follow scripture directly. For centuries, Sunni Muslims have practiced Islam through the framework of the four legal schools. The 20th century, however, witnessed the rise of individuals who denounced the legal schools, highlighting cases where they contradict texts from the Qur'ān or Sunna. These differences are exemplified in the heated debates between the Salafi ḥadīth scholar Muḥammad Nāṣir al-Dīn al-Albānīand his Traditionalist critics. This book examines the tensions between Salafis and Traditionalists concerning scholarly authority in Islam. Emad Hamdeh offers an insider's view of the debates between Salafis and Traditionalists and their differences regarding the correct method of interpreting Islam. He provides a detailed analysis of the rise of Salafism, the impact of the printing press, the role of scholars in textual interpretation, and the divergent approaches to Islamic law"--